The Implementation of Total Quality Management at Taman Siswa Elementary School - Riswandi, Riswandi; Hariri, Hasan; Nurwahidin, Muhammad; Utami, Nur Ridha (FKIP Universitas Lampung, 2024)
Abstract: The Implementation of Total Quality Management at Taman Siswa Elementary School. Objectives: This study aims to find out about the implementation of integrated quality management at Taman Siswa elementary school. Methods: This research method is a qualitative descriptive method with a case study type. Data collection techniques with interviews, observation, and documentation. The data analyzed refers to Miles and Huberman. The validity of the data used source triangulation and technique triangulation. Findings: The findings of the study indicate that the implementation of integrated quality management at Taman Siswa elementary school has been carried out well and there needs to be continuous improvement in various fields. Conclusion: So that by implementing integrated quality management at Taman Siswa elementary school, the quality of the school can be improved and can compete with other schools globally. Keywords: elementary school, management, quality, TQM.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202435